1995
DOI: 10.1007/bf00169063
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid receptors of the EP3 subtype mediate the inhibitory effect of prostaglandin E2 on noradrenaline release in the mouse brain cortex

Abstract: Mouse or rat brain cortex slices were preincubated with 3H-noradrenaline and superfused with physiological salt solution containing desipramine. We studied the effects of prostaglandin E2 (PGE2), prostaglandin D2 (PGD2) and related drugs on the electrically evoked (50 mA, 2 ms, 0.3 Hz) tritium overflow. PGE2 inhibited the electrically evoked tritium overflow from mouse brain cortex slices; the maximum effect of PGE2 (79%) was attenuated by the alpha 2-adrenoceptor agonist talipexole (to 52%) and enhanced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…Convergent evidence supports this hypothesis. In an in vitro study of the effects of prostaglandin E 2 on electrically-evoked tritiated norepinephrine overflow, Exner and Schlicker found that prostaglandin E 2 inhibited the electrically-evoked norepinephrine tritium overflow from mouse and rat brain cortex slices [59]. Data from an earlier similarly designed study were consistent with those obtained by Exner and Schlicker [111].…”
Section: Abstinence Symptoms Treatment Medicationssupporting
confidence: 71%
“…Convergent evidence supports this hypothesis. In an in vitro study of the effects of prostaglandin E 2 on electrically-evoked tritiated norepinephrine overflow, Exner and Schlicker found that prostaglandin E 2 inhibited the electrically-evoked norepinephrine tritium overflow from mouse and rat brain cortex slices [59]. Data from an earlier similarly designed study were consistent with those obtained by Exner and Schlicker [111].…”
Section: Abstinence Symptoms Treatment Medicationssupporting
confidence: 71%
“…Previous studies have shown that EP 3 receptors on presynaptic nerve terminals regulate the release of neurotransmitters (Exner and Schlicker, 1995;Nakamura et al, 1998;Schlicker and Marr, 1997). Whether EP 3 receptors are present on glutamatergic terminals of presynaptic sites of the dl-PAG has not, to our knowledge, been reported although EP 3 immunoreactivity has been identified in the dl-PAG (Ek et al, 2000;Nakamura et al, 2000).…”
Section: Discussionmentioning
confidence: 75%
“…Many pharmacologic studies have indicated that EP3R functions as a presynaptic receptor (Mantelli et al, 1991;Molderings et al, 1992Molderings et al, , 1994Exner and Schlicker, 1995;Reinheimer et al, 1998;Spicuzza et al, 1998). From the above-mentioned results of the dorsal rhizotomy experiments, it is inferred that the EP3R protein in the spinal dorsal horn is supplied through axons from dorsal root ganglion cells and is located on the presynaptic membrane.…”
Section: Synaptic Localization Of Ep3rmentioning
confidence: 99%